`Drive it like you Stole it́. Auto Theft and the Illusion of Normalcy - Cherbonneau, Michael (The British journal of criminology, 2006)
In line with recent interest in the criminal decision-making process, researchers have begun exploring the risks and rewards that offenders attach to specific forms of crime and how these perceptions guide their behaviour. In this paper, we examine the strategies that auto thieves use to avoid police detection while driving a stolen vehicle. To do this, we rely on semi-structured interviews with 54 auto thieves. Results indicate that auto thieves manage encounters with police by creating an illusion of normalcy. Auto thieves make decisions throughout the crime-commission process that allows them to present an image of a normal driver in a normal vehicle to deflect attention away from themselves and the stolen vehicle. These strategies allow them to hide in the open and still maintain the crime's rewards. Discussion focuses on restrictive deterrence and wider implications for arrest avoidance in decision-making research. ABSTRACT FROM AUTHOR